Applicability of Vacuum Impregnation to Modify Physico-Chemical, Sensory and Nutritive Characteristics of Plant Origin Products—A Review - Radziejewska-Kubzdela, Elżbieta (MDPI, 2014)
Vacuum impregnation is a non-destructive method of introducing a solution with a specific composition to the porous matrices of fruit and vegetables. Mass transfer in this process is a result of mechanically induced differences in pressure. Vacuum impregnation makes it possible to fill large volumes of intercellular spaces in tissues of fruit and vegetables, thus modifying physico-chemical properties and sensory attributes of products. This method may be used, e.g., to reduce pH and water activity of the product, change its thermal properties, improve texture, color, taste and aroma. Additionally, bioactive compounds may be introduced together with impregnating solutions, thus improving health-promoting properties of the product or facilitating production of functional food.